Utilizing Quizzes on the Duolingo to Promote Students Vocabulary Mastery - Rahma, Tanjila; Irianti, Leni (Universitas Galuh, 2024)
This research aims to find out the effectiveness of Duolingo games to help students' vocabulary mastery and describe students' perceptions of learning English using the Duolingo application. One of problems found in learning English is a lack of vocabulary that can make it difficult for students to understand texts, speak, listen, and write effectively. Limited student emphasis on acquiring vocabulary in class. In addition, schools that still use conventional learning methods make students bored. This research was conducted using qualitative methods using questionnaires and interviews to determine student perceptions. This research was conducted in one of Islamic senior High School in Tasikmalaya involving 33 students from class X participants. The results of this study indicate that students give a positive perception about the Duolingo application because most students (79%) agree more with learning English vocabulary using the Duolingo application as a medium of learning vocabulary. Apart from it, there are several advantages that can be drawn from using the Duolingo application as a medium for learning English vocabulary: 1) the Duolingo application make the students easy to understand the material; 2) the Duolingo application made the students more enthusiastic in learning English vocabulary; 3) the Duolingo application can eliminate boredom in learning; and 4) the Duolingo application encourage the students for generating new idea in learning.